Proceedings of the Workshop on Computational Approaches to Semitic Languages - Semitic '98 1998
DOI: 10.3115/1621753.1621755
|View full text |Cite
|
Sign up to set email alerts
|

Discovering lexical information by tagging Arabic newspaper text

Abstract: In this paper we describe a system for building an Arabic lexicon automatically by tagging Arabic newspaper text. In this system we are using several techniques for tagging the words in the text and figuring out their types and their features. The major techniques that we are using are: finding phrases, analyzing the affixes of the words, and analyzing their pattems. Proper nouns are particularly difficult to identify in the Arabic language; we describe techniques for isolating them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Hmeidi, Kanaan, and Evens () describe how to build an automatic indexing system for Arabic text with comparable accuracy to human indexing systems. In their study, Abuleil and Evens () show how to automatically build a large Arabic integrated and comprehensive lexicon. They developed a part of speech (POS) tagger for Arabic text to extract features of the Arabic words encountered.…”
Section: Related Workmentioning
confidence: 99%
“…Hmeidi, Kanaan, and Evens () describe how to build an automatic indexing system for Arabic text with comparable accuracy to human indexing systems. In their study, Abuleil and Evens () show how to automatically build a large Arabic integrated and comprehensive lexicon. They developed a part of speech (POS) tagger for Arabic text to extract features of the Arabic words encountered.…”
Section: Related Workmentioning
confidence: 99%
“…‫ﺷﻬﺮ‬ Month ‫ﻣﺪﻱﻨﺔ‬ city ‫ﺷﻤﺎل‬ north A proper noun is the name of a specific person, place, organization, thing, idea, event, date, time, or other entity. Some of them are solid (inert) nouns some of them are derived [Abuleil and Evens 1998].…”
Section: ‫ﻣﺤﺎﺿﺮ‬ Professormentioning
confidence: 99%
“…Several studies suggested that indexing Arabic text using roots significantly increases retrieval effectiveness over the use of words (Abuleil and Evens, 1998;Hammo et al, 2002;Habash and Rambow, 2005;Khoja, 1999;Al-Kharashi and Evens, 1994).…”
Section: Stemming-root Extractionmentioning
confidence: 99%
“…It is critical for parsing, text generation, text summarization and for question answering systems (Abuleil and Evens, 1998). Furthermore, Information Retrieval is one of the first areas of natural language processing in which statistics were successfully applied (Hiemstra and De vries, 2000).…”
Section: Introductionmentioning
confidence: 99%